Formulation Approaches of Triptans for Management of Migraine - Ahmed Kassem, Abeer (Current Drug Delivery, 2016)
Background: The use of triptans in the treatment of migraine was a breakthrough. Their selective agonistic action at serotonin (5-hydroxytryptamine) receptors has provided insights into the pathophysiology of migraine and represented a significant advance in migraine pharmacotherapy. Sumatriptan was the first synthesized triptan available for clinical use in the United States. Although it revolutionized the treatment of migraine, it demonstrated some drawbacks, e.g. poor oral bioavailability, erratic absorption, and high rate of headache recurrence. New triptans have been developed namely; almotriptan, zolmitriptan, rizatriptan, eletriptan, frovatriptan and naratriptan, with each one demonstrating specific pharmacokinetic parameters that may be translated into clinical advantage. Although second generation triptans possess better bioavailability compared to sumatriptan, they all still need improvement. Objective: This review illustrates a survey for the available researches aimed to enhance triptans’ bioavailability and hence effectiveness, either by investigating alternative routes of administration, other than oral route and/or designing appropriate formulations. Results: Promising results were gained by many researchers after studying different routes for triptans’ administration, e.g. nasal, buccal, sublingual, transdermal and pulmonary using well designed formulations, e.g. nanocarriers, microcarriers, orodispersible tablets or films, in situ gels, microneedles for transdermal application, etc. Conclusion: Utilizing alternative routes for triptans’ administration in addition to designing appropriate formulations, were successful approaches. However, further investigations should be conducted to establish their bioavailability and in vitro- in vivo correlation studies are also required, to confirm the potential of the designed formulations for use in humans, hence novel efficient triptans’ formulations may appear on the market in the near future.
Keywords: Bioavailability